Decarboxylated crosslinked polybenzoxazole gas separation membranes containing phthalazinone structure and preparation method thereof
Patent Information
- Application Number
- CN202611095329.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-22
- Publication Date
- 2026-10-13
AI Technical Summary
然而,由于热重排温度高于多数聚酰亚胺(PI)的玻璃化转变温度(Tg),因此在热重排反应发生之前,聚合物的链段运动被激发,引起分子链重新排布,导致聚合物膜出现严重收缩,薄膜趋于密实化,进而劣化分离膜的气体分离性能
本发明所制备的聚苯并噁唑气体分离膜具备高渗透通量、高选择性以及优异的抗塑化性能。相较于现有技术,本发明具有以下有益效果:
Smart Images

Figure CN122894875A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of gas separation and purification technology, specifically relating to a decarboxylation crosslinked polybenzoxazole gas separation membrane containing a diazanaphthone structure and its preparation method. Background Technology
[0002] In gas separation technology, compared with traditional separation technologies such as cryogenic separation, pressure swing adsorption, and amine absorption, membrane separation technology is gradually gaining attention due to its advantages such as no need for complex equipment, low energy consumption, controllable cost, small footprint, flexible operation, and environmental friendliness. This technology can achieve efficient separation under normal temperature and pressure conditions and is currently widely used in fields such as nitrogen enrichment, oxygen enrichment, hydrogen recovery, removal of acidic gases (such as H2S and CO2) from natural gas, and dehumidification of air and natural gas. It is gradually replacing high-energy-consuming traditional separation processes and has become a promising green separation technology.
[0003] In the field of membrane separation, research expert Robeson, through analysis of a large amount of data, pointed out that there is a trade-off relationship between the gas permeability and gas selectivity of polymer gas separation membranes. Journal of Membrane Science ,1991, 62, 165-185; Journal of Membrane Science [2008, 320, 390-400.] That is, high gas flux is often accompanied by low selectivity, and vice versa. Therefore, how to improve the gas permeability of polymer gas separation membranes without excessively sacrificing selectivity, or how to improve selectivity as much as possible while maintaining high flux, is a highly challenging research topic in this field.
[0004] Furthermore, in the natural gas purification process, to ensure purification efficiency, upstream pressures often reach tens or even hundreds of atmospheres. Simultaneously, natural gas contains CO2, trace hydrocarbons, and acidic impurities such as H2S. This can cause polymer separation membranes to become plasticized during operation, leading to a sharp decline in selectivity and a deterioration in separation performance. Therefore, industrial-grade separation not only places stringent requirements on the gas permeation rate and selectivity of the membrane, but also imposes high demands on the membrane's high-pressure resistance, long-term separation stability, and anti-fouling properties during service. Thus, developing a separation membrane material capable of achieving high throughput, high selectivity, and high stability under complex operating conditions is of significant practical importance and urgency.
[0005] In 1999, researchers Tullos et al. discovered that o-hydroxy polyimide (HPI) can undergo a thermal rearrangement reaction at high temperatures of 425-460 °C to generate polybenzoxazole (PBO). After HPI is transformed into thermally rearranged polybenzoxazole (TR-PBO), its chain segments tend to become disordered, and the relatively twisted molecular chains transform into rigid rod-shaped molecular chains, thereby increasing the free volume fraction of the polymer. FFV The removal of bulk intermediates and the release of CO2 during thermal rearrangement can create more microporous structures between molecular chains, further enhancing gas transport rates. However, because the thermal rearrangement temperature is higher than the glass transition temperature of most polyimides (PI), T g Therefore, before the thermal rearrangement reaction occurs, the chain segment motion of the polymer is excited, causing the molecular chains to rearrange, resulting in severe shrinkage of the polymer membrane, making the membrane tend to become denser, and thus deteriorating the gas separation performance of the separation membrane. Therefore, it is necessary to improve the polymer's... T g Setting the temperature above the thermal rearrangement reaction temperature is a key strategy for optimizing the performance of thermally rearranged polybenzoxazole gas separation membranes. Summary of the Invention
[0006] To address the above problems, this invention provides a decarboxylation-crosslinked polybenzoxazole gas separation membrane containing a diazanaphthone structure and its preparation method.
[0007] First, this invention provides a decarboxylation-crosslinked polybenzoxazole gas separation membrane containing a diazanaphthone structure, wherein the molecular structure of the gas separation membrane precursor has the following general formula:
[0008] (I) The mixture contains 50% molar fraction of diacid anhydride A residue with a diazanaphthone structure, 20%–40% molar fraction of carboxylated diamine B residue, and 30%–10% molar fraction of ortho-hydroxy diamine C residue, where m:n = 0.66–4.0.
[0009] The decarboxylated crosslinked polybenzoxazole gas separation membrane containing a diazanaphthone structure is prepared by decarboxylation crosslinking of the precursor shown in formula (I).
[0010] Furthermore, in the decarboxylation crosslinked polybenzoxazole gas separation membrane containing a diazanaphthone structure, the diacid anhydride A containing the diazanaphthone structure is any one or a combination of the following compounds, whose chemical structural formula is: .
[0011] Furthermore, in the decarboxylation crosslinked polybenzoxazole gas separation membrane containing a diazanaphthone structure, the carboxyl diamine B is any one or a combination of the following compounds, whose chemical structural formula is: .
[0012] Furthermore, in the decarboxylation crosslinked polybenzoxazole gas separation membrane containing a diazanaphthone structure, the ortho-hydroxy diamine C is any one or a combination of the following compounds, whose chemical structural formula is: .
[0013] The present invention also provides a method for preparing a decarboxylation crosslinked polybenzoxazole gas separation membrane containing a diazanaphthone structure as described above, the preparation method comprising the following steps: Step 1: Sequentially treat dicarboxylic acid anhydride A, carboxydiamine B, and o-hydroxydiamine C under vacuum at 80-150 °C for 6-12 hours; Step 2: Under the protection of an inert gas, add the diacid anhydride A, carboxydiamine B, o-hydroxydiamine C, catalyst D and high-boiling solvent E treated in Step 1 to a three-necked flask in sequence, stir and heat the reaction system to 50~100 ℃, and stir for 3~8 h. The total mass fraction of the dicarboxylic acid anhydride A, carboxydiamine B, and o-hydroxydiamine C in the reaction system is 10 w.t.%~30 wt%; The molar ratio of the dicarboxylic acid anhydride A, carboxydiamine B, and o-hydroxydiamine C is 0.5: x :(0.5- x ),in x The value range is 0.2 to 0.4; The molar ratio of the dicarboxylic acid anhydride A to the catalyst D is 1:1.5~4.0; Step 3: Under inert gas protection, add catalyst F and phosphorus-containing stabilizer G, heat the reaction system to 120~220 ℃, and continue stirring the reaction for 8~16 h; The amount of catalyst F is 5 wt% to 10 wt% of the mass of diacid anhydride A added; The amount of phosphorus-containing stabilizer G is 20 wt% to 50 wt% of the mass of diacid anhydride A added; Step 4: When the system is cooled to 15~35 ℃, the reaction solution is poured into alcohol H to precipitate fibrous solid product. The product is filtered and washed with alcohol H 2~4 times. Then the filter cake is extracted with alcohol H for 8~24 h. Finally, the filter cake is vacuum dried at 80~160 ℃ for 12~24 h to obtain polymer K. Step 5: Dissolve polymer K in solvent J, with the solid content controlled at 0.5 wt%~15 wt%, filter, and then pour onto a clean glass plate that has been pre-leveled; place the glass plate in a vacuum oven at 25~80 ℃ to evaporate the solvent for 10~72 h, then raise the temperature to 80~160 ℃ and vacuum dry for 6~12 h; after the temperature drops to 20~35 ℃, remove the film to obtain the gas separation membrane precursor; Step 6: Place the gas separation membrane precursor in a tube furnace and continuously purge the tube furnace with inert gas for 10-60 min to ensure the oxygen concentration is below 50 ppm; in the inert gas atmosphere, heat the tube furnace to 180-220 ℃ at a heating rate of 1-10 ℃ / min and hold for 0.5-4 h, then heat to 360-420 ℃ at a heating rate of 1-10 ℃ / min and hold for 0.5-5 h, then heat to 425-460 ℃ at a heating rate of 1-10 ℃ / min and hold for 0.5-3 h; after the temperature drops to 20-35 ℃, remove the membrane to obtain the decarboxylated crosslinked PBO gas separation membrane material.
[0014] Furthermore, in the method for preparing the decarboxylation crosslinked polybenzoxazole gas separation membrane containing a diazanaphthone structure, in step 2, the catalyst D is any one or a combination of benzoic acid, terephthalic acid, isophthalic acid, phthalic acid, p-methylbenzoic acid, m-methylbenzoic acid, o-methylbenzoic acid, p-ethylbenzoic acid, m-ethylbenzoic acid, o-ethylbenzoic acid, p-isopropylbenzoic acid, m-isopropylbenzoic acid, o-isopropylbenzoic acid, p-hydroxybenzoic acid, m-hydroxybenzoic acid, o-hydroxybenzoic acid, naphtholic acid, 4-phenylbenzoic acid, and 3-phenylbenzoic acid; The high-boiling-point solvent E is any one or a combination of phenol, p-cresol, m-cresol, o-cresol, p-ethylphenol, m-ethylphenol, o-ethylphenol, 2,4-dimethylphenol, 2,3-dimethylphenol, 2,6-dimethylphenol, 2,5-dimethylphenol, 3,5-dimethylphenol, and 3,4-dimethylphenol.
[0015] Furthermore, in the preparation method of the decarboxylation crosslinked polybenzoxazole gas separation membrane containing a diazanaphthone structure, in step 3, the catalyst F is any one or a combination of tert-butylpyridine, quinoline, 6-methylquinoline, 4-methylquinoline, isoquinoline, and 8-methylisoquinoline. The phosphorus-containing stabilizer G is any one or a combination of triphenyl phosphite, triphenyl phosphate, triphenyl phosphorus, and triphenyl phosphorus oxide.
[0016] Furthermore, in the method for preparing the decarboxylation crosslinked polybenzoxazole gas separation membrane containing a diazonaphthone structure, in step 4, the alcohol H is any one or a combination of methanol, ethanol, and isopropanol.
[0017] Furthermore, in the preparation method of the decarboxylation crosslinked polybenzoxazole gas separation membrane containing a diazanaphthone structure, in step 5, the solvent J is any one or a combination of chloroform, dichloromethane, tetrahydrofuran, dioxane, acetonitrile, ethyl acetate, acetone, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, and γ-butyrolactone.
[0018] Furthermore, in the method for preparing the decarboxylation crosslinked polybenzoxazole gas separation membrane containing a diazanaphthone structure, in step 6, after purging the tubular furnace with an oxygen / nitrogen mixed gas flow, the oxygen concentration inside the tubular furnace is less than 50 ppm.
[0019] Beneficial effects The polybenzoxazole gas separation membrane prepared by this invention possesses high permeation flux, high selectivity, and excellent anti-plasticization properties. Compared with the prior art, this invention has the following beneficial effects: (1) A functional dianhydride monomer that is more conducive to improving porosity was selected. Based on extensive experimental data comparison and analysis, this invention selected a rigid non-coplanar acid anhydride containing a diazanaphthone structure. The diazanaphthone structure not only possesses stronger rigidity and more prominent steric hindrance, but its non-coplanar characteristic can effectively inhibit close packing of molecular chains and significantly increase the free volume content (…). FFV Furthermore, the diazanaphthone structure is rich in tertiary amine nitrogen atoms, which enhances the affinity of the polymer backbone for CO2, thus facilitating the simultaneous increase of CO2 permeation flux and CO2 / CH4 selectivity. (2) The structure of the six-membered diazanaphthone has better chemical stability than that of the five-membered imide heterocycle, which provides a strong guarantee for the long-term stable operation of the separation membrane under the complex working conditions of natural gas purification, and lays a reliable foundation for the membrane material to move from the laboratory to industrial application. (3) Combining decarboxylation crosslinking and thermally induced rearrangement in the same separation membrane system can improve the efficiency of membrane separation. T g This invention suppresses the shrinkage effect of the membrane material during thermal rearrangement, achieving a synergistic improvement in gas permeation flux and selectivity of the separation membrane. Furthermore, it utilizes decarboxylation crosslinking technology to achieve chemical crosslinking between polymer molecular chains, significantly enhancing the polymer's... T g It inhibits the chain segment movement caused by high temperature during thermal rearrangement, preserves the microporous structure created by thermal rearrangement, and improves the skeletal stability and anti-plasticization ability of the membrane. (4) The synergistic regulation of membrane material microstructure and separation performance was achieved. This invention, through precise control of the molar ratio of carboxydiamine to o-hydroxydiamine, reveals the effect of their ratio on the PI precursor. T g The influence of thermal rearrangement on the gas separation performance of polybenzoxazole membranes. Attached Figure Description
[0020] Figure 1 The following are the anti-plasticization properties of gas separation membranes prepared in several examples: (a) Examples 1, 2, and 3; (b) Examples 4, 5, and 6; (c) Examples 7, 8, and 9. Figure 2 The following are comparisons of the CO2 / CH4 separation performance of gas separation membranes prepared in several examples with the Robeson upper limit: (a) Examples 4, 5, and 6, (b) Examples 7, 8, 9, 10, 11, and 12. Detailed Implementation
[0021] The present invention is described in detail through the following embodiments. It should be understood that the following embodiments are merely illustrative and explanatory of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are covered within the scope of protection of the present invention.
[0022] Example 1 As a comparative example, this embodiment provides a method for preparing a polybenzoxazole film containing PZDA-1 and OHDA-1, wherein PZDA-1 and OHDA-1 have the following structures: ,
[0023] Specifically, the following steps are included: 2.12 g of PZDA-1 and 0.56 g of OHDA-1 were vacuum-treated at 80 °C for 12 h. After cooling to room temperature, they were added sequentially to a 100 mL three-necked flask under argon protection, along with 1.66 g of terephthalic acid and 7.5 g of p-cresol. The reaction system was stirred and heated to 80 °C for 8 h. Subsequently, 0.16 g of 6-methylquinoline and 0.71 g of triphenyl phosphite were added, and the reaction system was heated to 200 °C and stirred for another 16 h. When the system cooled to 30 °C, it was poured into ethanol to precipitate a fibrous solid product. The product was filtered, and the filter cake was washed three times with ethanol. The filter cake was then extracted with ethanol for 12 h, and finally dried under vacuum at 80 °C for 12 h to obtain 2.4 g of polymer (89% yield). 0.6 g of the polymer was dissolved in 11.4 g of chloroform (5 wt% solids), filtered, and then dripped onto a clean, leveled glass plate. The glass plate was placed in a vacuum oven at 30 °C to evaporate the solvent for 18 h, then the temperature was raised to 80 °C and vacuum dried for 6 h. After the temperature dropped to 25 °C, a polyimide precursor film was obtained. The gas separation membrane precursor was placed in a tube furnace and continuously purged with inert gas for 20 min to ensure that the oxygen concentration was below 50 ppm. In the inert gas atmosphere, the tube furnace was heated to 200 °C at a heating rate of 5 °C / min and held for 1 h, then heated to 400 °C at a heating rate of 5 °C / min and held for 1 h, and then heated to 450 °C at a heating rate of 5 °C / min and held for 1 h. After the temperature dropped to 25 °C, the film was removed to obtain the PBO gas separation membrane material. The gas separation performance and anti-plasticization performance are shown in Table 1 and Table 2, respectively. Figure 1 As shown, the film shrinks significantly after heat treatment, resulting in poor gas separation performance and resistance to plasticization.
[0024] Example 2 As a comparative example, this embodiment provides a method for preparing a polybenzoxazole film comprising PZDA-1, m-phenylenediamine, and OHDA-1, wherein PZDA-1 and OHDA-1 have the following structures: ,
[0025] Specifically, the following steps are included: 2.12 g of PZDA-1, 0.17 g of m-phenylenediamine, and 0.34 g of OHDA-1 were treated under vacuum at 80 °C for 12 h. After cooling to room temperature, they were added sequentially to a 100 mL three-necked flask under argon protection, along with 1.66 g of terephthalic acid and 7.5 g of p-cresol. The reaction system was stirred and heated to 80 °C for 8 h. Subsequently, 0.16 g of 6-methylquinoline and 0.71 g of triphenyl phosphite were added, and the reaction system was heated to 200 °C and stirred for another 16 h. When the system cooled to 30 °C, it was poured into ethanol to precipitate a fibrous solid product. The product was filtered, and the filter cake was washed three times with ethanol. The filter cake was then extracted with ethanol for 12 h, and finally dried under vacuum at 80 °C for 12 h to obtain 2.3 g of polymer (87% yield). 0.6 g of polymer was dissolved in 11.4 g of chloroform (solid content 5 wt%), filtered, and then poured onto a clean, leveled glass plate. The glass plate was placed in a vacuum oven at 30 ℃ to evaporate the solvent for 18 h, then the temperature was raised to 80 ℃ and vacuum dried for 6 h. After the temperature dropped to 25 ℃, a polyimide precursor film was obtained. The gas separation membrane precursor was placed in a tube furnace, and the furnace was continuously purged with inert gas for 20 min to ensure that the oxygen concentration was below 50 ppm. In the inert gas atmosphere, the tube furnace was heated to 200 ℃ at a heating rate of 5 ℃ / min and held for 1 h, then heated to 400 ℃ at a heating rate of 5 ℃ / min and held for 1 h, then heated to 450 ℃ at a heating rate of 5 ℃ / min and held for 1 h. After the temperature dropped to 25 ℃, the film was removed to obtain the PBO gas separation membrane material. The gas separation performance and anti-plasticization performance are shown in Table 1 and Table 2, respectively. Figure 1 As shown, the film shrinks significantly after heat treatment, resulting in poor gas separation performance and resistance to plasticization.
[0026] Example 3 This embodiment provides a method for preparing a polybenzoxazole film comprising PZDA-1, CDA-1, and OHDA-1, wherein PZDA-1, CDA-1, and OHDA-1 each have the following structures: , ,
[0027] Specifically, the following steps are included: 2.12 g of PZDA-1, 0.24 g of CDA-1, and 0.34 g of OHDA-1 were vacuum-treated at 80 °C for 12 h. After cooling to room temperature, they were sequentially added to a 100 mL three-necked flask under argon protection, along with 1.66 g of terephthalic acid and 7.5 g of p-cresol. The reaction system was stirred and heated to 80 °C for 8 h. Subsequently, 0.16 g of 6-methylquinoline and 0.71 g of triphenyl phosphite were added, and the reaction system was heated to 200 °C and stirred for another 16 h. When the system cooled to 30 °C, it was poured into ethanol to precipitate a fibrous solid product. The product was filtered, and the filter cake was washed three times with ethanol. The filter cake was then extracted with ethanol for 12 h, and finally dried under vacuum at 80 °C for 12 h to obtain 2.4 g of polymer (89% yield). 0.6 g of polymer was dissolved in 11.4 g of chloroform (solid content 5 wt%), filtered, and then poured onto a clean, pre-leveled glass plate. The glass plate was placed in a vacuum oven at 30 ℃ to evaporate the solvent for 18 h, and then the temperature was raised to 80 ℃ for vacuum drying for 6 h. After the temperature dropped to 25 ℃, a polyimide precursor film was obtained. The gas separation membrane precursor was placed in a tube furnace, and the tube furnace was continuously purged with inert gas for 20 min to ensure that the oxygen concentration was below 50 ppm. In an inert gas atmosphere, the tube furnace was heated to 200 ℃ at a heating rate of 5 ℃ / min and held for 1 h, then heated to 400 ℃ at a heating rate of 5 ℃ / min and held for 1 h, and then heated to 450 ℃ at a heating rate of 5 ℃ / min and held for 1 h. After the temperature dropped to 25 ℃, the film was removed to obtain the decarboxylated and crosslinked PBO gas separation membrane material. Gas separation performance and anti-plasticization performance are shown in Table 1 and Table 2, respectively. Figure 1 As shown, the shrinkage of the film is significantly reduced after heat treatment, and the gas separation performance and anti-plasticization performance are greatly improved.
[0028] Table 1
[0029] The comparative results of Examples 1-3 show that directly polymerizing anhydrides containing diazanaphthone structures with carboxyl-free diamines results in films that shrink severely after heat treatment and exhibit poor gas separation performance. This invention, by introducing carboxyl groups for decarboxylation crosslinking, significantly improves the rigidity of the polymer chains, suppresses film shrinkage during thermal rearrangement, and endows the final thermally rearranged polymer film with excellent gas separation performance and resistance to plasticization.
[0030] Example 4 In comparison, this embodiment provides a method for preparing a polybenzoxazole film comprising PZDA-2, CDA-3, and OHDA-7, wherein PZDA-2, CDA-3, and OHDA-7 each have the following structures: , ,
[0031] Specifically, the following steps are included: 2.39 g of PZDA-2, 0.13 g of CDA-3, and 0.83 g of OHDA-7 were vacuum-treated at 80 °C for 12 h. After cooling to room temperature, they were sequentially added to a 100 mL three-necked flask under argon protection, along with 1.63 g of m-methylbenzoic acid and 10 g of o-cresol. The reaction system was stirred and heated to 80 °C for 8 h. Subsequently, 0.21 g of 4-methylquinoline and 0.65 g of triphenylphosphine were added, and the reaction system was heated to 180 °C and stirred for another 16 h. When the system cooled to 35 °C, it was poured into methanol to precipitate a fibrous solid product. The product was filtered, and the filter cake was washed three times with methanol. The filter cake was then extracted with methanol for 12 h, and finally dried under vacuum at 80 °C for 12 h to obtain 3.0 g of polymer (89% yield). 0.6 g of polymer was dissolved in 5.4 g of N,N-dimethylformamide (solid content 10 wt%), filtered, and then poured onto a clean, pre-leveled glass plate. The glass plate was placed in a vacuum oven at 60 ℃ to evaporate the solvent for 72 h, and then the temperature was raised to 120 ℃ for vacuum drying for 8 h. After the temperature dropped to 25 ℃, a polyimide precursor film was obtained. The gas separation membrane precursor was placed in a tube furnace, and the tube furnace was continuously purged with inert gas for 30 min to ensure that the oxygen concentration was below 50 ppm. In an inert gas atmosphere, the tube furnace was heated to 180 ℃ at a heating rate of 5 ℃ / min and held for 1 h, then heated to 380 ℃ at a heating rate of 5 ℃ / min and held for 2 h, and then heated to 425 ℃ at a heating rate of 5 ℃ / min and held for 1.5 h. After the temperature dropped to 25 ℃, the film was removed to obtain the decarboxylated and crosslinked PBO gas separation membrane material. Anti-plasticization properties and gas separation properties are respectively as follows: Figure 1 and Figure 2 As shown, the film still shrinks after heat treatment, and its anti-plasticization properties and gas separation properties are not ideal.
[0032] Example 5 In comparison, this embodiment provides a method for preparing a polybenzoxazole film comprising PZDA-2, CDA-3, and OHDA-7, wherein PZDA-2, CDA-3, and OHDA-7 each have the following structures: , ,
[0033] Specifically, the following steps are included: 2.39 g of PZDA-2, 0.60 g of CDA-3, and 0.10 g of OHDA-7 were vacuum-treated at 80 °C for 12 h. After cooling to room temperature, they were sequentially added to a 100 mL three-necked flask under argon protection, along with 1.63 g of m-methylbenzoic acid and 10 g of o-cresol. The reaction system was stirred and heated to 80 °C for 8 h. Subsequently, 0.21 g of 4-methylquinoline and 0.65 g of triphenylphosphine were added, and the reaction system was heated to 180 °C and stirred for another 16 h. When the system cooled to 35 °C, it was poured into methanol to precipitate a fibrous solid product. The product was filtered, and the filter cake was washed three times with methanol. The filter cake was then extracted with methanol for 12 h, and finally dried under vacuum at 80 °C for 12 h to obtain 2.7 g of polymer (87% yield). 0.6 g of polymer was dissolved in 5.4 g of N,N-dimethylformamide (solid content 10 wt%), filtered, and then poured onto a clean, pre-leveled glass plate. The glass plate was placed in a vacuum oven at 60 ℃ to evaporate the solvent for 72 h, and then the temperature was raised to 120 ℃ for vacuum drying for 8 h. After the temperature dropped to 25 ℃, a polyimide precursor film was obtained. The gas separation membrane precursor was placed in a tube furnace, and the tube furnace was continuously purged with inert gas for 30 min to ensure that the oxygen concentration was below 50 ppm. In an inert gas atmosphere, the tube furnace was heated to 180 ℃ at a heating rate of 5 ℃ / min and held for 1 h, then heated to 380 ℃ at a heating rate of 5 ℃ / min and held for 2 h, and then heated to 425 ℃ at a heating rate of 5 ℃ / min and held for 1.5 h. After the temperature dropped to 25 ℃, the film was removed to obtain the decarboxylated and crosslinked PBO gas separation membrane material. Anti-plasticization properties and gas separation properties are respectively as follows: Figure 1 and Figure 2 As shown, the film did not show significant shrinkage after heat treatment and exhibited excellent resistance to plasticization, but its gas separation performance was not ideal.
[0034] Example 6 This embodiment provides a method for preparing a polybenzoxazole film comprising PZDA-2, CDA-3, and OHDA-7, wherein PZDA-2, CDA-3, and OHDA-7 each have the following structures: , ,
[0035] Specifically, the following steps are included: 2.39 g of PZDA-2, 0.33 g of CDA-3, and 0.52 g of OHDA-7 were vacuum-treated at 80 °C for 12 h. After cooling to room temperature, they were sequentially added to a 100 mL three-necked flask under argon protection, along with 1.63 g of m-methylbenzoic acid and 10 g of o-cresol. The reaction system was stirred and heated to 80 °C for 8 h. Subsequently, 0.21 g of 4-methylquinoline and 0.65 g of triphenylphosphine were added, and the reaction system was heated to 180 °C and stirred for another 16 h. When the system cooled to 35 °C, it was poured into methanol to precipitate a fibrous solid product. The product was filtered, and the filter cake was washed three times with methanol. The filter cake was then extracted with methanol for 12 h, and finally dried under vacuum at 80 °C for 12 h to obtain 2.8 g of polymer (86% yield). 0.6 g of polymer was dissolved in 5.4 g of N,N-dimethylformamide (solid content 10 wt%), filtered, and then poured onto a clean, pre-leveled glass plate. The glass plate was placed in a vacuum oven at 60 ℃ to evaporate the solvent for 72 h, and then the temperature was raised to 120 ℃ for vacuum drying for 8 h. After the temperature dropped to 25 ℃, a polyimide precursor film was obtained. The gas separation membrane precursor was placed in a tube furnace, and the tube furnace was continuously purged with inert gas for 30 min to ensure that the oxygen concentration was below 50 ppm. In an inert gas atmosphere, the tube furnace was heated to 180 ℃ at a heating rate of 5 ℃ / min and held for 1 h, then heated to 380 ℃ at a heating rate of 5 ℃ / min and held for 2 h, and then heated to 425 ℃ at a heating rate of 5 ℃ / min and held for 1.5 h. After the temperature dropped to 25 ℃, the film was removed to obtain the decarboxylated and crosslinked PBO gas separation membrane material. Anti-plasticization properties and gas separation properties are respectively as follows: Figure 1 and Figure 2 As shown, the film did not show significant shrinkage after heat treatment, and exhibited excellent gas separation performance and resistance to plasticization.
[0036] Glass transition temperatures of PI precursors prepared in Examples 4, 5, and 6 and PI after decarboxylation crosslinking ( T g See Table 2: Table 2
[0037] The comparative results of Examples 4-6 show that the gas separation membranes prepared in Examples 4 and 5 have poor gas separation performance due to the suboptimal molar ratio of carboxydiamine to o-hydroxydiamine. This invention, by precisely controlling the molar ratio of carboxydiamine and o-hydroxydiamine, determined the optimal range and obtained excellent overall gas separation performance. Simultaneously, the membrane exhibits good high-pressure resistance to plasticization, providing an effective technical means to overcome the "trade-off" effect.
[0038] Example 7 This embodiment provides a method for preparing a polybenzoxazole film comprising PZDA-9, CDA-2, and OHDA-4, wherein PZDA-9, CDA-2, and OHDA-4 have the following structures: , ,
[0039] Specifically, the following steps are included: 2.39 g of PZDA-9, 0.27 g of CDA-2, and 0.88 g of OHDA-4 were vacuum-treated at 90 °C for 8 h. After cooling to room temperature, they were sequentially added to a 100 mL three-necked flask under argon protection, along with 1.09 g of p-methylbenzoic acid and 13 g of m-cresol. The reaction system was stirred and heated to 80 °C for 8 h. Subsequently, 0.19 g of isoquinoline and 0.54 g of triphenylphosphine oxide were added, and the reaction system was heated to 160 °C and stirred for another 12 h. When the system cooled to 25 °C, it was poured into methanol to precipitate a fibrous solid product. The product was filtered, and the filter cake was washed three times with methanol. The filter cake was then extracted with methanol for 16 h, and finally dried under vacuum at 80 °C for 16 h to obtain 3.1 g of polymer (88% yield). 0.6 g of polymer was dissolved in 5.4 g of N,N-dimethylacetamide (solid content 10 wt%), filtered, and then poured onto a clean, pre-leveled glass plate. The glass plate was placed in a vacuum oven at 60 ℃ to evaporate the solvent for 72 h, and then the temperature was raised to 120 ℃ for vacuum drying for 10 h. After the temperature dropped to 25 ℃, a polyimide precursor film was obtained. The gas separation membrane precursor was placed in a tube furnace, and the tube furnace was continuously purged with inert gas for 30 min to ensure that the oxygen concentration was below 50 ppm. In an inert gas atmosphere, the tube furnace was heated to 200 ℃ at a heating rate of 5 ℃ / min and held for 1 h, then heated to 400 ℃ at a heating rate of 5 ℃ / min and held for 1 h, and then heated to 450 ℃ at a heating rate of 5 ℃ / min and held for 1 h. After the temperature dropped to 25 ℃, the film was removed to obtain the decarboxylated and crosslinked PBO gas separation membrane material.
[0040] Example 8 In comparison, this embodiment provides a method for preparing a polybenzoxazole film comprising PZDA-9, CDA-2, and OHDA-4, wherein PZDA-9, CDA-2, and OHDA-4 each have the following structures: , ,
[0041] Specifically, the following steps are included: 2.39 g of PZDA-9, 0.40 g of CDA-2, and 0.59 g of OHDA-4 were treated under vacuum at 90 °C for 8 h. After cooling to room temperature, they were added sequentially to a 100 mL three-necked flask under argon protection, along with 1.09 g of p-methylbenzoic acid and 13 g of m-cresol. The reaction system was stirred and heated to 80 °C for 8 h. Subsequently, 0.19 g of isoquinoline and 0.54 g of triphenylphosphine oxide were added, and the reaction system was heated to 160 °C and stirred for another 12 h. When the system cooled to 25 °C, it was poured into methanol to precipitate a fibrous solid product. The product was filtered, and the filter cake was washed three times with methanol. The filter cake was then extracted with methanol for 16 h, and finally dried under vacuum at 80 °C for 16 h to obtain 2.9 g of polymer (86% yield). 0.6 g of polymer was dissolved in 5.4 g of N,N-dimethylacetamide (solid content 10 wt%), filtered, and then poured onto a clean, pre-leveled glass plate. The glass plate was placed in a vacuum oven at 60 ℃ to evaporate the solvent for 72 h, and then the temperature was raised to 120 ℃ for vacuum drying for 10 h. After the temperature dropped to 25 ℃, a polyimide precursor film was obtained. The gas separation membrane precursor was placed in a tube furnace, and the tube furnace was continuously purged with inert gas for 30 min to ensure that the oxygen concentration was below 50 ppm. In an inert gas atmosphere, the tube furnace was heated to 200 ℃ at a heating rate of 5 ℃ / min and held for 1 h, then heated to 400 ℃ at a heating rate of 5 ℃ / min and held for 1 h, and then heated to 450 ℃ at a heating rate of 5 ℃ / min and held for 1 h. After the temperature dropped to 25 ℃, the film was removed to obtain the decarboxylated and crosslinked PBO gas separation membrane material.
[0042] Example 9 In comparison, this embodiment provides a method for preparing a polybenzoxazole film comprising PZDA-9, CDA-2, and OHDA-4, wherein PZDA-9, CDA-2, and OHDA-4 each have the following structures: , ,
[0043] Specifically, the following steps are included: 2.39 g of PZDA-9, 0.53 g of CDA-2, and 0.29 g of OHDA-4 were treated under vacuum at 90 °C for 8 h. After cooling to room temperature, they were sequentially added to a 100 mL three-necked flask under argon protection, along with 1.09 g of p-methylbenzoic acid and 13 g of m-cresol. The reaction system was stirred and heated to 80 °C for 8 h. Subsequently, 0.19 g of isoquinoline and 0.54 g of triphenylphosphine oxide were added, and the reaction system was heated to 160 °C and stirred for another 12 h. When the system cooled to 25 °C, it was poured into methanol to precipitate a fibrous solid product. The product was filtered, and the filter cake was washed three times with methanol. The filter cake was then extracted with methanol for 16 h, and finally dried under vacuum at 80 °C for 16 h to obtain 2.8 g of polymer (yield 87%). 0.6 g of polymer was dissolved in 5.4 g of N,N-dimethylacetamide (solid content 10 wt%), filtered, and then poured onto a clean, pre-leveled glass plate. The glass plate was placed in a vacuum oven at 60 ℃ to evaporate the solvent for 72 h, and then the temperature was raised to 120 ℃ for vacuum drying for 10 h. After the temperature dropped to 25 ℃, a polyimide precursor film was obtained. The gas separation membrane precursor was placed in a tube furnace, and the tube furnace was continuously purged with inert gas for 30 min to ensure that the oxygen concentration was below 50 ppm. In an inert gas atmosphere, the tube furnace was heated to 200 ℃ at a heating rate of 5 ℃ / min and held for 1 h, then heated to 400 ℃ at a heating rate of 5 ℃ / min and held for 1 h, and then heated to 450 ℃ at a heating rate of 5 ℃ / min and held for 1 h. After the temperature dropped to 25 ℃, the film was removed to obtain the decarboxylated and crosslinked PBO gas separation membrane material.
[0044] Example 10 In comparison, this embodiment provides a method for preparing a polybenzoxazole film comprising PZDA-15, CDA-20, and OHDA-15, wherein PZDA-15, CDA-20, and OHDA-15 each have the following structures: , ,
[0045] Specifically, the following steps are included: 2.66 g of PZDA-15, 0.55 g of CDA-20, and 0.45 g of OHDA-15 were treated under vacuum at 90 °C for 8 h. After cooling to room temperature, they were sequentially added to a 100 mL three-necked flask under argon protection, along with 1.22 g of benzoic acid and 13 g of m-cresol. The reaction system was stirred and heated to 80 °C for 8 h. Subsequently, 0.18 g of isoquinoline and 0.85 g of triphenylphosphine oxide were added, and the reaction system was heated to 160 °C and stirred for another 12 h. When the system cooled to 25 °C, it was poured into methanol to precipitate a fibrous solid product. The product was filtered, and the filter cake was washed three times with methanol. The filter cake was then extracted with methanol for 16 h, and finally dried under vacuum at 80 °C for 16 h to obtain 3.1 g of polymer (85% yield). 0.6 g of polymer was dissolved in 5.4 g of N,N-dimethylacetamide (solid content 10 wt%), filtered, and then poured onto a clean, pre-leveled glass plate. The glass plate was placed in a vacuum oven at 60 ℃ to evaporate the solvent for 72 h, and then the temperature was raised to 120 ℃ for vacuum drying for 10 h. After the temperature dropped to 25 ℃, a polyimide precursor film was obtained. The gas separation membrane precursor was placed in a tube furnace, and the tube furnace was continuously purged with inert gas for 30 min to ensure that the oxygen concentration was below 50 ppm. In an inert gas atmosphere, the tube furnace was heated to 200 ℃ at a heating rate of 5 ℃ / min and held for 1 h, then heated to 400 ℃ at a heating rate of 5 ℃ / min and held for 1 h, and then heated to 450 ℃ at a heating rate of 5 ℃ / min and held for 1 h. After the temperature dropped to 25 ℃, the film was removed to obtain the decarboxylated and crosslinked PBO gas separation membrane material.
[0046] Example 11 In comparison, this embodiment provides a method for preparing a polybenzoxazole film comprising PZDA-11, CDA-28, and OHDA-6, wherein PZDA-11, CDA-28, and OHDA-6 each have the following structures: , ,
[0047] Specifically, the following steps are included: 2.46 g of PZDA-11, 1.01 g of CDA-28, and 0.39 g of OHDA-6 were treated under vacuum at 90 °C for 8 h. After cooling to room temperature, they were added sequentially to a 100 mL three-necked flask under argon protection, along with 1.22 g of benzoic acid and 13 g of m-cresol. The reaction system was stirred and heated to 80 °C for 8 h. Subsequently, 0.18 g of isoquinoline and 0.85 g of triphenylphosphine oxide were added, and the reaction system was heated to 160 °C and stirred for another 12 h. When the system cooled to 25 °C, it was poured into methanol to precipitate a fibrous solid product. The product was filtered, and the filter cake was washed three times with methanol. The filter cake was then extracted with methanol for 16 h, and finally dried under vacuum at 80 °C for 16 h to obtain 3.4 g of polymer (88% yield). 0.6 g of polymer was dissolved in 5.4 g of N,N-dimethylacetamide (solid content 10 wt%), filtered, and then poured onto a clean, pre-leveled glass plate. The glass plate was placed in a vacuum oven at 60 ℃ to evaporate the solvent for 72 h, and then the temperature was raised to 120 ℃ for vacuum drying for 10 h. After the temperature dropped to 25 ℃, a polyimide precursor film was obtained. The gas separation membrane precursor was placed in a tube furnace, and the tube furnace was continuously purged with inert gas for 30 min to ensure that the oxygen concentration was below 50 ppm. In an inert gas atmosphere, the tube furnace was heated to 200 ℃ at a heating rate of 5 ℃ / min and held for 1 h, then heated to 400 ℃ at a heating rate of 5 ℃ / min and held for 1 h, and then heated to 450 ℃ at a heating rate of 5 ℃ / min and held for 1 h. After the temperature dropped to 25 ℃, the film was removed to obtain the decarboxylated and crosslinked PBO gas separation membrane material.
[0048] Example 12 In comparison, this embodiment provides a method for preparing a polybenzoxazole film comprising PZDA-4, CDA-31, and OHDA-20, wherein PZDA-4, CDA-31, and OHDA-20 each have the following structures: , ,
[0049] Specifically, the following steps are included: 2.19 g of PZDA-4, 0.77 g of CDA-31, and 0.61 g of OHDA-20 were treated under vacuum at 90 °C for 8 h. After cooling to room temperature, they were sequentially added to a 100 mL three-necked flask under argon protection, along with 1.22 g of benzoic acid and 13 g of m-cresol. The reaction system was stirred and heated to 80 °C for 8 h. Subsequently, 0.18 g of isoquinoline and 0.85 g of triphenylphosphine oxide were added, and the reaction system was heated to 160 °C and stirred for another 12 h. When the system cooled to 25 °C, it was poured into methanol to precipitate a fibrous solid product. The product was filtered, and the filter cake was washed three times with methanol. The filter cake was then extracted with methanol for 16 h, and finally dried under vacuum at 80 °C for 16 h to obtain 3.1 g of polymer (yield 87%). 0.6 g of polymer was dissolved in 5.4 g of N,N-dimethylacetamide (solid content 10 wt%), filtered, and then poured onto a clean, pre-leveled glass plate. The glass plate was placed in a vacuum oven at 60 ℃ to evaporate the solvent for 72 h, and then the temperature was raised to 120 ℃ for vacuum drying for 10 h. After the temperature dropped to 25 ℃, a polyimide precursor film was obtained. The gas separation membrane precursor was placed in a tube furnace, and the tube furnace was continuously purged with inert gas for 30 min to ensure that the oxygen concentration was below 50 ppm. In an inert gas atmosphere, the tube furnace was heated to 200 ℃ at a heating rate of 5 ℃ / min and held for 1 h, then heated to 400 ℃ at a heating rate of 5 ℃ / min and held for 1 h, and then heated to 450 ℃ at a heating rate of 5 ℃ / min and held for 1 h. After the temperature dropped to 25 ℃, the film was removed to obtain the decarboxylated and crosslinked PBO gas separation membrane material.
[0050] Experimental results show that the glass transition temperature of the PI precursor film prepared in the embodiments of the present invention can reach above 400 °C after decarboxylation crosslinking (Examples 5 and 6). After decarboxylation crosslinking and thermal rearrangement, the permeability coefficients of the polybenzoxazole film for CO2 and CH4 are respectively... P (CO2) = 61.1 barrer, P (CH4) = 0.73 barrer, the ideal selectivity for CO2 / CH4 gas pairs can reach α (CO2 / CH4) = 84, exceeding the Robeson limit in 2008 (Example 8), and the film did not plasticize in a high-pressure CO2 environment of 30 bar, demonstrating good resistance to plasticization (Examples 7, 8, and 9).
[0051] Extensive experiments have confirmed that the molar ratio of carboxylated diamine to o-hydroxylated diamine has a significant impact on the gas separation performance of the final polybenzoxazole (PBO) film: When the carboxylated diamine content is high, the film has a high crosslinking density before thermal rearrangement, but this leads to a reduction in the proportion of hydroxyl groups that can participate in subsequent thermal rearrangement, ultimately resulting in a lower benzoxazole structure content, which is detrimental to improving overall gas separation performance. Similarly, when the o-hydroxylated diamine content is high, a large number of benzoxazole structures can increase CO2 permeability, but due to insufficient crosslinking density in the precursor film, lower chain rigidity and... T g The inability to suppress membrane shrinkage during thermal rearrangement leads to a decrease in the final separation membrane's selectivity for CO2 / CH4. Through extensive experimental research and data comparison, this invention found that when the molar ratio of dicarboxylic anhydride A, carboxydiamine B, and o-hydroxydiamine C is 0.5: x :(0.5- x ),in x When the value ranges from 0.2 to 0.4, the CO2 permeability and CO2 / CH4 selectivity are synergistically improved, reaching the standard for practical industrial applications.
Claims
1. A decarboxylation-crosslinked polybenzoxazole gas separation membrane containing a diazanaphthone structure, characterized in that, The molecular structure of the gas separation membrane precursor has the following general formula: (Ⅰ) The mixture contains 50% molar fraction of diacid anhydride A residue with a diazanaphthone structure, 20%–40% molar fraction of carboxylated diamine B residue, and 30%–10% molar fraction of ortho-hydroxy diamine C residue, where m:n = 0.66–4.
0.
2. The decarboxylation-crosslinked polybenzoxazole gas separation membrane containing a diazanaphthone structure according to claim 1, wherein the dicarboxylic acid anhydride A containing the diazanaphthone structure is any one or a combination of the following compounds, and its chemical structural formula is: 。 3. The decarboxylation crosslinked polybenzoxazole gas separation membrane containing a diazanaphthone structure according to claim 1, wherein the carboxyl diamine B is any one or a combination of the following compounds, and its chemical structural formula is: 。 4. The decarboxylation-crosslinked polybenzoxazole gas separation membrane containing a diazanaphthone structure according to claim 1, wherein the o-hydroxy diamine C is any one or a combination of the following compounds, and its chemical structural formula is: 。 5. A method for preparing a decarboxylation-crosslinked polybenzoxazole gas separation membrane containing a diazanaphthone structure as described in any one of claims 1-4, characterized in that, The preparation method includes the following steps: Step 1: Sequentially treat diacid anhydride A, carboxydiamine B, and o-hydroxydiamine C under vacuum at 80-150 °C for 6-12 h; Step 2: Under the protection of an inert gas, add the diacid anhydride A, carboxydiamine B, o-hydroxydiamine C, catalyst D and high-boiling solvent E treated in Step 1 to a three-necked flask in sequence, stir and heat the reaction system to 50~100 ℃, and stir for 3~8 h. The total mass fraction of the dicarboxylic acid anhydride A, carboxydiamine B, and o-hydroxydiamine C in the reaction system is 10 wt% to 30 wt%. The molar ratio of the dicarboxylic acid anhydride A, carboxydiamine B, and o-hydroxydiamine C is 0.5: x :(0.5- x ),in x The value range is 0.2 to 0.4; The molar ratio of the dicarboxylic acid anhydride A to the catalyst D is 1:1.5~4.0; Step 3: Under inert gas protection, add catalyst F and phosphorus-containing stabilizer G, heat the reaction system to 120~220℃, and continue stirring the reaction for 8~16 h; The amount of catalyst F is 5 wt% to 10 wt% of the mass of diacid anhydride A added; The amount of phosphorus-containing stabilizer G is 20 wt% to 50 wt% of the mass of diacid anhydride A added; Step 4: When the system is cooled to 15~35 ℃, the reaction solution is poured into alcohol H to precipitate fibrous solid product. The product is filtered and washed with alcohol H 2~4 times. Then the filter cake is extracted with alcohol H for 8~24 h. Finally, the filter cake is vacuum dried at 80~160 ℃ for 12~24 h to obtain polymer K. Step 5: Dissolve polymer K in solvent J, with the solid content controlled at 0.5 wt%~15 wt%, filter, and then pour onto a clean glass plate that has been pre-leveled; place the glass plate in a vacuum oven at 25~80 ℃ to evaporate the solvent for 10~72 h, then raise the temperature to 80~160 ℃ and vacuum dry for 6~12 h; after the temperature drops to 20~35 ℃, remove the film to obtain the gas separation membrane precursor; Step 6: Place the gas separation membrane precursor in a tube furnace and continuously purge the tube furnace with inert gas for 10-60 min to ensure the oxygen concentration is below 50 ppm; in the inert gas atmosphere, heat the tube furnace to 180-220 ℃ at a heating rate of 1-10 ℃ / min and hold for 0.5-4 h, then heat to 360-420 ℃ at a heating rate of 1-10 ℃ / min and hold for 0.5-5 h, then heat to 425-460 ℃ at a heating rate of 1-10 ℃ / min and hold for 0.5-3 h; after the temperature drops to 20-35 ℃, remove the membrane to obtain the decarboxylated crosslinked PBO gas separation membrane material.
6. The method for preparing the decarboxylation crosslinked polybenzoxazole gas separation membrane containing a diazanaphthone structure according to claim 5, wherein in step 2, the catalyst D is any one or a combination of benzoic acid, terephthalic acid, isophthalic acid, phthalic acid, p-methylbenzoic acid, m-methylbenzoic acid, o-methylbenzoic acid, p-ethylbenzoic acid, m-ethylbenzoic acid, o-ethylbenzoic acid, p-isopropylbenzoic acid, m-isopropylbenzoic acid, o-isopropylbenzoic acid, p-hydroxybenzoic acid, m-hydroxybenzoic acid, o-hydroxybenzoic acid, naphtholic acid, 4-phenylbenzoic acid, and 3-phenylbenzoic acid; The high-boiling-point solvent E is any one or a combination of phenol, p-cresol, m-cresol, o-cresol, p-ethylphenol, m-ethylphenol, o-ethylphenol, 2,4-dimethylphenol, 2,3-dimethylphenol, 2,6-dimethylphenol, 2,5-dimethylphenol, 3,5-dimethylphenol, and 3,4-dimethylphenol.
7. The method for preparing a decarboxylation crosslinked polybenzoxazole gas separation membrane containing a diazanaphthone structure according to claim 5, wherein in step 3, the catalyst F is any one or a combination of tert-butylpyridine, quinoline, 6-methylquinoline, 4-methylquinoline, isoquinoline, and 8-methylisoquinoline; The phosphorus-containing stabilizer G is any one or a combination of triphenyl phosphite, triphenyl phosphate, triphenyl phosphorus, and triphenyl phosphorus oxide.
8. The method for preparing the decarboxylation crosslinked polybenzoxazole gas separation membrane containing a diazanaphthone structure according to claim 5, wherein in step 4, the alcohol H is any one or a combination of methanol, ethanol, and isopropanol.
9. The method for preparing the decarboxylation crosslinked polybenzoxazole gas separation membrane containing a diazanaphthone structure according to claim 5, wherein in step 5, the solvent J is any one or a combination of chloroform, dichloromethane, tetrahydrofuran, dioxane, acetonitrile, ethyl acetate, acetone, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, and γ-butyrolactone.
10. The method for preparing a decarboxylation crosslinked polybenzoxazole gas separation membrane containing a diazanaphthone structure according to claim 5, wherein in step 6, after purging the tubular furnace with an oxygen / nitrogen mixed gas flow, the oxygen concentration inside the tubular furnace is less than 50 ppm.